Taxation, R&D tax incentives and patent application in Europe - Christof Ernst; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The focus of this paper is on effects from tax incentives for research and development inputs (R&D) and corporate income tax on business R&D and patenting behaviour. First, we provide a theoretical discussion of tax planning with R&D and intellectual property (IP) ownership. Further, we employ firm-specific micro-data on patent applications of European corporations at the European Patent Office to test reactions on changes in R&D tax incentives and corporate tax burden. We find a positive impact of R&D tax incentives and a negative impact of the statutory corporate income tax rate on patenting. R&D incentives rather influence the tendency to invest in R&D, whereas the tax burden rather influences the scale of R&D investment and the count of patent applications.
urn:nbn:de:bsz:180-madoc-31691
Keywords: H25; H26; O30; 330; Patent; R&D; Tax Incentives; Taxation; EU